2013
DOI: 10.4251/wjgo.v5.i7.127
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic staging in hilar cholangiocarcinoma: Is it still justified?

Abstract: Radical resection remains the only potential curative therapy for hilar cholangiocarcinoma (HCCA). The aim of staging laparoscopic (SL) is to identify patients with previously undetected advanced disease who will not benefit from surgical palliation and therefore avoid unnecessary laparotomies. The accuracy of non-invasive imaging techniques has significantly improved during the last years. As a consequence, the diagnostic yield of SL of biliary tract malignancy should have decreased proportionally. At the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Actually, there is no consensus about the usefulness of DL in patients with HC. A recent review [23] reported that OY and AC have decreased through the years from 41 and 72 %, respectively, to 14 and 32 % in the more recent series. This limited value of DL in the last years was confirmed in a large single series of 175 patients, [24] and it is likely the result of imaging techniques improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, there is no consensus about the usefulness of DL in patients with HC. A recent review [23] reported that OY and AC have decreased through the years from 41 and 72 %, respectively, to 14 and 32 % in the more recent series. This limited value of DL in the last years was confirmed in a large single series of 175 patients, [24] and it is likely the result of imaging techniques improvement.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvements in diagnostic CT/MR, the yield of staging laparoscopy in changing the management in patients with hilar cholangiocarcinoma has decreased to 13-17%. 66,67 Song et al and Nagino et al have not described regular use of staging laparoscopy in their studies. However, Jarnagin et al have shown selective use in patients with Blumgart T2 and T3 lesions, or if there is advanced disease on preoperative imaging.…”
Section: Staging Laparoscopymentioning
confidence: 99%
“…The role of laparoscopic exploration (LE) decreased over time together with the increase of sensibility and specificity of imaging techniques. Routine LE is not recommended, but it can be useful in T2/T3 pCCC according to AJCC classification or type III and IV according to Bismuth-Corlette[ 92 , 109 ]. LE is the only way to detect peritoneal metastasis prior to laparotomy, due to the low predictive value of non-invasive technique.…”
Section: Treatmentmentioning
confidence: 99%